Seroprevalence of Neospora caninum in repeat breeder dairy cows in Turkey - Simsek, Sami; Utuk, Armagan Erdem; Koroglu, Ergun; Dumanli, Nazir; Risvanli, Ali (Archiv Fur Tierzucht, 2008)
Sera samples from 89 dairy, cows with repeat breeder and 94 healthy pregnant dairy cows (controls) from Elazig province of eastern Turkey were tested for presence of Neospora caninum antibodies by use of a competitive enzyme linked immunosorbent assay (cELISA). Fifteen out of 183 cows tested (8.19%) were found to be seropositive to N. caninum antibody. Overall, seroprevalence of . caninum was significantly higher (P<0.05) in dairy cows with repeat breeder ( 13.48%, 12/89) thin in dairy cows with healthy pregnant (3.19%, 3/94). There was no statistically significant relationship between seroprevalence and breed and age groups in cows with repeat breeder (P>0.05). In conclusion, the current study highlights the importance of N. caninum in cows with repeat breeder.
Keywords: Neospora caninum; infertility; repeat breeder; seroprevalence